THE APPLICATION OF GEOGEBRA SOFTWARE FOR SOLVING ALGEBRAIC PROBLEMS WITH A PARAMETER - Vira, Maryna; Samusenko, Petro (Physical and Mathematical Education, 2023)
Formulation of the problem. It is known that solving problems with a parameter is a powerful means of activating the cognitive activity of students. It also helps to generalize and systematize the knowledge. They encourage students to improve their level of mathematical competence. That is why the tasks with parameters are an important component of a school mathematics course at a professional level. Lots of sections of textbooks and several methodical manuals are devoted to them. Materials and methods. The investigation is based on the author’s experience of a long time of practical work with students of institutions of general secondary education. It is also a result of processing different informational sources, conducting reasoning of deductive character, and formulating conclusions.Results. The article provides an overview of such manuals, as well as articles in periodicals, which are devoted to both traditional methods of solving problems with a parameter (analytical and graphical methods), as well as the author's attempts to combine the traditional approach with modern means of teaching mathematics. The authors of this article propose for consideration several problems with the parameter, the solution of which involves a combination of an algorithmic approach with the ability to demonstrate a dynamic model of the considered problem in the GeoGebra environment. In our opinion, this approach to teaching will ensure the implementation of not only mathematical but also informational competencies of the student, which is an extremely important combination in the conditions of the reform of the NUS in secondary schools. During the teaching of algebra, the GeoGebra system is used as a tool for visualizing the studied mathematical objects, and expressions, and illustrating construction methods; as an environment for modeling and empirical research of the properties of the studied objects; as a complex that provides the user with a set of specialized tools for creating and transforming an object. Conclusions. We hope that the proposed material will be useful to both novice teachers and experienced teachers for teaching algebra classes, as it allows you to navigate the modern methodological literature on this topic and to look into the creative workshop of leading scientists in the field of mathematics teaching methods, who willingly share their ideas and experience in scientific articles.
Keywords: GeoGebra; equation with a parameter; a system of equations with a parameter; solution algorithm